Oral vinorelbine plus cisplatin versus pemetrexed plus cisplatin as first-line treatment of advanced non-squamous non-small-cell lung cancer: cost minimization analysis in 12 European countries - Grossi, Francesco; Bennouna, Jaafar; Havel, Libor; Hochmair, Maximillian; Almodovar, Teresa (Current medical research and opinion, 2016)
OBJECTIVE: A combination of vinorelbine and cisplatin is a standard treatment in non-small-cell lung cancer; oral vinorelbine is registered in 45 countries. Pemetrexed and cisplatin are recommended in front-line chemotherapy of non-squamous non-small-cell lung cancer (NS-NSCLC). The objective of this study was to conduct a cost minimization analysis from the perspective of the national health service (NHS) in each of 12 European countries, based on a randomized phase II study in NS-NSCLC (NAVoTRIAL01), with 100 oral vinorelbine plus cisplatin patients (arm A) and 51 pemetrexed plus cisplatin patients (arm B). RESEARCH DESIGN AND METHODS: Country-specific costs and DRG codes considered included those relating to anticancer drugs, administration settings (out-patient/in-patient/at home), serious adverse events (defined as involving hospitalization and considered due to anticancer drugs) and concomitant medications. Relevant costs were calculated based on country-specific reimbursement procedures and official tariffs. MAIN OUTCOME MEASURES: Cost and savings per patient. RESULTS: Using the NHS perspective, savings per patient treated with oral vinorelbine ranged from €1317 (Denmark) to €35,001 (Germany). Expressed as percentages, savings per patient treated with oral vinorelbine compared with pemetrexed ranged between 5% (France) and 83% (Czech Republic). Pooled average costs for each treatment arm across the 12 countries resulted in cost savings for payers of €12,871, favoring oral vinorelbine plus cisplatin. CONCLUSIONS: Given the reported efficacy with both regimens, this pan-European economic analysis provides compelling evidence supporting oral vinorelbine use over pemetrexed for the treatment of NS-NSCLC. Oral vinorelbine provides similar efficacy and an easily manageable safety profile at lower overall cost per patient treated, combined with an easier/more convenient mode of administration. Sensitivity analysis across varied scenarios demonstrated the robustness of the results. The principle weakness of our study was its reliance upon a single small scale study to provide efficacy data, since this is the only study conducted in this specific population of patients. Further large scale trials are needed to confirm these results.
Keywords: NSCLC; Europe; Cisplatin; Evropa; cisplatina; Cost minimization; nádory plic; Antineoplastic Agents; náklady a analýza nákladů; Vinorelbine; nemalobuněčný karcinom plic; protinádorové látky; Humans; Carcinoma, Non-Small-Cell Lung; Pemetrexed; Vinblastine; vinorelbin; Costs and Cost Analysis; Lung Neoplasms; lidé; vinblastin